Development and Assessment of a Social Network Service-Based Lifestyle-Modification Program for Workers at High Risk of Developing Cardiovascular Disease. (March 2020) - Woo, Soo Hee; Oh, Eui Geum; Kim, Kyung-SOO; Chu, Sang Hui; Kim, Gwang Suk; Nam, Chung Mo
Cardiovascular disease is a leading cause of mortality in the United States. This study examined the cardiovascular disease risk factors and health beliefs of workers for the purpose of developing a social network service (SNS)-based (e.g., Facebook and KakaoTalk) lifestyle-modification program for workers. Participants included 68 hospital workers (aged 25-60 years), with more than two metabolic syndrome or cardiovascular disease risk factors. Participants were randomly assigned to one of three groups: SNS intervention group ( n = 23), education-only intervention group ( n = 19), or nonintervention group ( n = 26). Data were collected to compare changes in risk indicators according to the intervention method and time and analyzed using repeated-measures analyses of variance. Compared to the education and nonintervention groups, the SNS intervention group demonstrated significant improvements in waist circumference, body mass index, total cholesterol, low-density lipoprotein cholesterol, health promotion behaviors, and self-efficacy. This type of program has potential for allowing occupational health professionals to work with workers to improve lifestyle behaviors that promote health and reduce the risk of cardiovascular disease.